ANALISIS PERSEPSI PENONTON TERHADAP IKLAN MULTIKULTURAL "SASA HADIRKAN RASA UNTUK INDONESIA" - Irenia Jastisia; Fidrotul Jamilah; Nur Azizah Puji Astuti; Candra Krida Mustika; Egaputra Twedapinta (JADECS (Journal of Art, Design, Art Education and Culture Studies))
"Sasa Hadirkan Rasa untuk Indonesia" is one of Sasa's commercials shown using a two-dimensional method. Sasa's commercials contain multicultural concepts that are reflected in Japanese animation style, European MIDI music, and culinary culture content in Indonesia. This study used data collection methods in the form of interviews and literature studies. This research aims to: 1) analyze the incorporation of Indonesian cultural elements in typical Japanese animation styles and musical backgrounds with the use of European MIDI music; 2) analyze audience perception of three-cultural collaboration in Sasa advertising; 3) provide a reference in the form of innovation for the development of advertising in Indonesia. This study analyzed the Sasa animated advertising video version of "Sasa Hadirkan Rasa for Indonesia" which had been broadcast in 2021 through social media Youtube. Interviews were conducted on men and women aged 20-35 in Indonesia. To support research data, literature studies focus on audience perception, multicultural advertising, and advertising. Based on analysis it was found that Sasa's commercials were interesting because they reflected international multicultural culture in two-dimensional animation.